AN ADAPTIVE DIFFERENTIAL EVOLUTION ALGORITHM WITH A BOUND ADJUSTMENT STRATEGY FOR SOLVING NONLINEAR PARAMETER IDENTIFICATION PROBLEMS - Wongsa, Watchara; Puphasuk, Pikul; Wetweerapong, Jeerayut (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
Real-world parameter identification problems require determining the bounds that cover the unknown solutions. This paper presents an adaptive differential evolution algorithm with a bound adjustment strategy (ADEBAS) for solving nonlinear parameter identification problems. The adjustment strategy detects the parameter-bound violations of mutant vectors during the evolution process and gradually extends the bounds. The algorithm adaptively uses two mutation strategies and two ranges of crossover rate to balance the population diversity and convergence speed. Experimental results show that ADEBAS can solve 24 nonlinear regression tasks from the National Institute of Standards and Technology benchmark with accurate estimation and reliability. It also outperforms the compared methods on real-world parameter identification problems.